Music Audiences 3.0: Concert-Goers’ Psychological Motivations at the Dawn of Virtual Reality - Charron, Jean-Philippe (Frontiers in Psychology, 2017)
Reviewing consumers’ motivations to attend performances in a continuously evolving social and technological context is essential because live concerts generate an important and growing share of revenues for the music industry. Evolving fans’ preferences and technological innovations constantly alter the way music is distributed and consumed. In a marketing 3.0 era, what consumers do with music is becoming more significant than simply owning or listening to a song. These changes are not only blurring the lines between production and consumption (i.e., co-creation), but also distorting the concept of live attendance altogether. Although mediated performances typically lack presence and authenticity, recent advances in immersive technologies, such as spherical videos and virtual reality goggles, could represent a new form of experiencing live music.